Phytoplankton Species Diversity Patterns and Associated Driving Factors in China’s Jiulong River Estuary: Roles That Nutrients and Nutrient Ratios Play - Ge, Feiyang; Ma, Zhiyuan; Chen, Bin; Wang, Yu; Lu, Xiaoqian; An, Shenqun; Zhang, Dian; Zhang, Wanting; Yu, Weiwei; Han, Wenxuan; Yu, Xingguang; Liu, Zhenghua; et al. (Frontiers in Marine Science, 2022)
Understanding diversity patterns and associated driving factors are the critical topics in macroecology and conservation biology. Phytoplankton are highly susceptible to environmental changes in estuaries, particularly eutrophication. This study examined phytoplankton alpha and beta diversity using investigation data in May (springtime), August (summer) and November (autumn) 2009 in China’s Jiulong River estuary, where it was easily polluted because of considerable discharge from a highly dense human population and low self-purification capacity with its limited river basin area, potentially resulting in eutrophication and then influencing phytoplankton diversity. Potential influencing factors were also explored, including DO, salinity, nutrients, nutrient ratios, geographic and hydrologic distance, and so on. The results indicated that Shannon’s index (H’) and Pielou’s index (J) decreased from the estuary’s upper middle and then increased from middle to lower reaches, Simpson’s (D) observed the opposite trend and species number (S) gradually increased from the estuary’s upper to lower reaches. For beta diversity, all the indices showed a gradual decrease trend from the estuary’s upper to lower reaches, where also, turnover dominated beta diversity for all seasons. It is noteworthy that the significant roles that nutrients and nutrient ratios played in shaping phytoplankton diversity patterns and the nutrient balance were characterized by excess nitrogen (N) and silicon (Si) and limited phosphorus (P), which could potentially cause diatom blooms. Findings also showed that decreasing Si concentrations can help to reduce overall pollution levels as well as the restoration of the estuary’s ecosystem better than just reducing N alone. Accordingly, this study advocates for the protection of the entire estuary system with particular emphasis on its upper reaches. Moreover, greater attention should also be paid to impacts associated with N input and nutrient ratio trade-offs to the prospective watershed management of this estuary. This study provides a practical approach to exploring estuarine diversity in a comprehensive way, which can inform effective biodiversity conservation and also be applied to other marine ecosystems to better guide sustainable management and conservation practices.